Design and simulation of a fuel cell-battery hybrid power system for extended-endurance quadrotor UAVs - Kayaoglu, Murat; Unal, Sencer; Biyik, Hilal (Pergamon-Elsevier Science Ltd, 2026)
The increasing utilization of UAVs has intensified the demand for efficient and environmentally sustainable power systems. This study proposes a hybrid power system that integrates a Proton Exchange Membrane Fuel Cell with a Li-Po battery to extend flight endurance. The PEMFC offers advantages such as high energy density, low emissions, and operational reliability, while the Li-Po battery ensures rapid power delivery during transient conditions. The central research question addressed in this study is whether a hybrid PEMFC-Li-Po power system can significantly extend the endurance of a small quadrotor UAV compared to a battery-only configuration, while maintaining system feasibility for real world applications. The system was modeled and simulated using MATLAB Simscape, which provides a physics-based environment for component-level validation. A rule-based energy management strategy was implemented to coordinate power flow between the PEMFC and the battery. Comparative simulations show that the hybrid UAV achieves a flight duration of approximately 165 min over six times longer than a battery-only configuration. These findings confirm that the proposed hybrid approach significantly enhances endurance and energy efficiency, representing a viable step toward sustainable UAV design.
Keywords: Quadrotor; PEMFC; Unmanned aerial vehicle; Power management; Simscape